Using Action Research to Address Poor Waste Management at Kijjabwemi C/U Primary School in Kijjabwemi Suburb, Masaka City. - Bukirwa, Fortunate Stella; Ssenyondwa , Denis; Muteesasira , Edrisa; Ssekyene , Caesar Bob; Muwanguzi , Samuel; Kabaalu , Moses; Muhunde , George; Orit , Robert; Nassolo , Susan; Sseguya , Gerald; Namukwaya, Olivia; Andinda , Maureen (Student’s Journal of Health Research Africa, 2022)
Background: This action research (AR) project was carried out at Kijjabwemi C/U Primary school at Kijjabwemi suburb of Kimaanya-Kabonera division of the newly formed Masaka City to identify, analyze, prioritize and identify solutions to address a health problem of priority at this setting using the locally accessible and available resources. Methodology: A participatory rural appraisal approach (PRA) guided how this research achieved its objectives right from the collection of information about the health challenges faced by this school. Data was collected using Focus group discussions, interviewing, and transect walk methods. Although the majority of data is qualitative, quantitative data is as well used especially where voting on an issue took place. At prioritization, a two-phase approach conceptualized by 1) multi-level voting techniques and 2) the Hanlon method of specifying criteria, PEARL testing, and Priority scoring was adopted to priorities the most urgent, serious, and feasible problem. The five Why/What for the root cause analysis was used to analyze the problem. Results: Out of the twelve health problems enlisted as urgent and serious by over 50% of stakeholders in the first phase, Poor waste management was identified as a major and priority problem caused by the excessive distance between generation and final disposal point, lack of designated collection points as well as containers, time and irregularity of disposal, shallow waste disposal pit and lack of well develop enforceable guidelines. Conclusion and recommendation: Stakeholder-centered- learning about excellent waste management practices, utilizing transferable plastic bins of 40ml capacity, increasing the depth of the disposal pit as well as fencing it, and developing settings-oriented guidelines to increase vigilance for waste generation reduction, frequency of disposal, and burning of waste was implemented as interventions.